The Role of Business Innovation in Mediating Digital Transformation and Marketing Strategy on SME Business Performance - Heida Ifkari Safitri; Agung Winarno; Wening Patmi Rahayu (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2026)
As a measure of business success, the performance of SMEs now faces challenges from rapid digitalisation and demands for more adaptive marketing strategies. This study aims to analyse the influence of digital transformation and marketing strategy on business performance, with business innovation as a mediating variable in tempe chip SMEs in Kampung Sanan, Malang City. The study uses a quantitative causality approach with an ex post facto explanatory method. The research population consists of 500 SMEs, with a sample of 245 SMEs selected purposively according to criteria. Data were collected through a 1–5 Likert scale questionnaire and analysed using Path Analysis with SmartPLS 4. The results show that digital transformation and marketing strategy have a positive and significant effect on business innovation and business performance. Business innovation also mediates the relationship between the two and business performance, although the mediation contribution is smaller than the direct effect. These findings confirm that the application of digital technology and adaptive marketing strategies, supported by innovation, can improve SME performance in a sustainable manner. The practical implication is that SMEs need to develop technology-based innovations, optimise social media, and formulate adaptive marketing strategies to strengthen their competitiveness.